Exploring Students’ Difficulties in Learning Listening Comprehension at Second Semester English Education Department of Muhammadiyah University of Makassar - Permatasari, Nurinda; Khaerati Syam, Ummi; Sastrawati, Ika (Journal of Language Testing and Assessment, 2023)
The results of the research from questionnaires and FGD showed that there were seven difficulties faced by students when studying listening comprehension based on listening material factors. First, the difficulty of unfamilliar words. 50% of students have this difficulty because they lack vocabulary. second, the difficulty of unfamiliar topics. students find it difficult when trying to understand the discourse, 40% experienced by students. third, difficulties in interpreting the meaning of spoken texts, especially when dealing with words that have multiple meanings, were also experienced by 40% of students in this study. fourth, difficulty due to the length of the spoken text which causes loss of concentration and motivation of students due to boredom, 60% of students find it difficult with the length of the spoken text. fifth, the difficulty in the type of input (eg the type of input from direct teaching by the lecturer) the fact that the listening comprehension class faced by the respondents was an online class, which made students experience various problems such as disruption of the teaching and learning process. the process of receiving information from lecturers due to unstable networks in some areas. sixth, 60% of students face difficulties in verbal instruction, because lecturers or native speakers have different accents and the last is difficulty in understanding when the speaker speaks very fast, based on the findings of this study it was found that the speaker's speaking speed is a difficulty experienced by all students.